2013
DOI: 10.1007/s00401-013-1225-3
|View full text |Cite
|
Sign up to set email alerts
|

TERT promoter mutation and aberrant hypermethylation are associated with elevated expression in medulloblastoma and characterise the majority of non-infant SHH subgroup tumours

Abstract: The childhood brain tumour medulloblastoma comprises four molecular disease subgroups (MB WNT , MB SHH , MB Group3 and MB Group4 ). However, large-scale whole-exome sequencing investigations have not identified defining genetic lesions for the non-MB WNT subgroups [8,11]. Recent studies reported in this journal and others [1,3,6,7,9] have identified frequent TERT promoter mutations and aberrant DNA methylation in CNS malignancies, suggesting an important mechanism in tumour development ( Figure 1a). In medullo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 11 publications
3
25
0
2
Order By: Relevance
“…Thus, the machinery maintaining the immortal phenotype in these two classes of cancers is distinct. Reduced 5mC in the TERT promoter has been reported previously for isolated subtypes of cancers with −124 mutations (Fan et al, 2016; Lindsey et al, 2014), although the allele specificity of 5mC has not previously been reported. Our analyses of large datasets of clinical samples broaden these findings to numerous cancers across many tissue types and provide a mechanistic rationale for how DNA methylation may effect TERT gene silencing in −124 cancers.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, the machinery maintaining the immortal phenotype in these two classes of cancers is distinct. Reduced 5mC in the TERT promoter has been reported previously for isolated subtypes of cancers with −124 mutations (Fan et al, 2016; Lindsey et al, 2014), although the allele specificity of 5mC has not previously been reported. Our analyses of large datasets of clinical samples broaden these findings to numerous cancers across many tissue types and provide a mechanistic rationale for how DNA methylation may effect TERT gene silencing in −124 cancers.…”
Section: Discussionmentioning
confidence: 78%
“…Although pediatric TERT promoter mutations are rare, a single study has reported TERT promoter hypermethylation in association with increased TERT expression in pediatric high-grade gliomas [50]. Aberrant TERT promoter methylation with increased TERT expression has been reported in other cancer types [51, 52, 53]. In adult gliomas TERT promoter mutation rather than promoter methylation is the predominant mechanism for TERT upregulation [54].…”
Section: Mutations and Other Alterations In Genes Affecting Telomere mentioning
confidence: 99%
“…showed that coexistence of TERT promoter and BRAF or NRAS mutations was associated with a 2-fold reduced rate of disease-free survival and a 5-fold reduced rate of melanoma-specific survival in patients with stage I and II melanoma26. TERT promoter hypermethylation is also an effective molecular marker for prognosis in a number of cancer types, and was previously shown to correlate with increased TERT expression in a subset of melanomas2933373839.…”
Section: Discussionmentioning
confidence: 98%